Complexation of biologically essential (mono- and divalent) metal cations to cucurbiturils: a DFT/SMD evaluation of the key factors governing the host–guest recognition. Issue 47 (27th July 2020) - Kircheva, Nikoleta; Dobrev, Stefan; Dasheva, Lyubima; Koleva, Iskra; Nikolova, Valya; Angelova, Silvia; Dudev, Todor
Abstract : Interaction between CB[ n ] ( n = 5–8) and biologically essential mono- and divalent metal cation. Abstract : Supramolecular complexes based on classical synthetic macrocyclic host molecules such as cyclodextrins and calixarenes have received much attention recently due to their broad applications as biological and chemical sensors, bioimaging agents, drug delivery carriers, light-emitting materials, etc. Cucurbit[ n ]urils comprise another group of cavitands known for their high affinity for various guest molecules. Nonetheless, some aspects of their coordination chemistry remain enigmatic. Although they are recognized as potential biomimetic scaffolds, they are still not tested as metalloenzyme models and not much is known about their metal-binding properties. Furthermore, there is no systematic study on the key factors controlling the processes of metal coordination to these systems. In the computational study herein, DFT molecular modeling has been employed in order to investigate the interactions of biologically essential (mono- and divalent) metal cations to cucurbit[ n ]urils and evaluate the major determinants shaping the process. The thermodynamic descriptors (Gibbs energies in the gas phase and in a water medium) of the corresponding complexation reactions have been estimated. The results obtained shed light on the mechanism of host–guest recognition and disclose which factors more specifically affect the metal binding process.